Industrial Property Rights and the Protection of Trade Secrets in the Russian Federation - Eräpohja, Mikko (My University, 2005)
This research examines the patent right, the trademark right and the protection of Trade secrets in Russia for Raisio Group. Its main task is to introduce the laws and the current practices, governing the field. Moreover this research pays attention to relevant international treaties which have had a great effect on the field. For example, treaties such as the Patent Cooperation Treaty (PCT), the Eurasian Patent Convention and the Madrid Agreement on the International Registration of Marks will be introduced, because of their usefulness and practicality when seeking protection in Russia. In many ways, the Russian patent law is in accordance with its western counterparts. In Russia a patent can be applied through the national application procedure. Furthermore the PCT procedure and the Eurasian patent application procedure make the applying for patents in many countries at the same time possible. The law is also otherwise developed. For example, the licensing of patents is possible if it otherwise covers the requirements, stipulated by the law. Also the Russian trademark law has progressed in the recent years. Russia’s membership to the Madrid Agreement and the Protocol allows also an applicant to apply for a trademark in many countries simultaneously. Besides it is possible to register an appellation of origin and a well–known trademark. Russia’s first law on the protection of trade secrets came into force on July 2004. Furthermore competition laws, the criminal and the civil code contain regulations, concerning the field. The new law is considered to be a step in the right direction. For example, employee is obliged not to disclose confidential information for three years after the possible termination of employment. The law also specifies employer’s obligations to hand over trade secrets to authorities. Even though the text of law in the field of this research has developed considerably in Russia in the past decade, unfortunately the practice has not always followed in the same pace. Peculiarities and problems still exist, which this research clarifies.
Keywords: intellectual property rights; patent right; trademark right and the protection of trade secrets in the Russian Federation; fi=Talousoikeus|en=Business Law|